Pegaruh Edukasi Keluarga Terhadap Tingkat Pengetahuan dan Kesiapan Merawat Pasien Gagal Ginjal Kronik: Literature Review - Maulia Dewi; Sutantri Sutantri; Titih Huriah (Malahayati Nursing Journal, 2026)
ABSTRACT Chronic kidney failure (CKD) is a chronic disease with increasing prevalence and is a global public health problem. This disease is characterized by a progressive and irreversible decline in kidney function, requiring long-term treatment such as hemodialysis, peritoneal dialysis, or conservative therapy. This condition impacts not only the patient's physical well-being but also the psychological, social, and economic well-being of both the patient and their family. This literature review aims to analyze and synthesize research findings related to the influence of family education on the level of knowledge and preparedness of families in caring for patients with chronic kidney failure. This can serve as a basis for developing family-based bereavement interventions and improving the quality of healthcare services. This literature review aims to examine the scientific evidence related to the influence of early post-operative mobilization on patient recovery. This study used a literature review design to examine the influence of family education on the level of knowledge and preparedness of families caring for patients with chronic kidney failure. Articles were searched through several scientific databases, including Google Scholar, PubMed, and ScienceDirect. Keywords used in the article search included family education, family knowledge, caregiving readiness, chronic kidney failure, and English equivalents such as family education, knowledge, caregiver readiness, and chronic kidney disease. Inclusion criteria for this literature review included research articles discussing family education in patients with chronic kidney failure, using a quantitative or qualitative research design, available in full text, and published within the last ten years. Articles that were irrelevant to the topic, not available in full text, or were opinion pieces or case reports were excluded from the review. The article selection process involved several stages: identifying articles based on the title and abstract, assessing the suitability of the article content to the research objectives, and reviewing the full text. Articles that met the inclusion criteria were then analyzed narratively. Extracted data included the author and year of publication, study design, sample size, the type of family education intervention, and research findings related to the level of knowledge and preparedness to care for patients with chronic kidney disease. Data analysis was conducted by comparing and synthesizing the results of selected studies to obtain a comprehensive overview of the effect of family education on the level of knowledge and preparedness to care for patients with chronic kidney disease. The literature review also showed variations in the effectiveness of education influenced by the delivery method, duration of education, and family characteristics. Continuous education using a combination of methods tended to provide more optimal results than one-time education or education without supporting media. Based on the literature review, it can be concluded that family education has a positive effect on increasing the level of knowledge and preparedness of families in caring for patients with chronic kidney disease. Structured and ongoing family education can improve family understanding of the disease and its treatment, as well as enhance family readiness to fulfill their role as caregivers. Keywords: Chronic Kidney Disease, Caregiver Education, Caregiving Readiness, Media. ABSTRAK Gagal ginjal kronik (GGK) merupakan salah satu penyakit kronik yang prevalensinya terus meningkat dan menjadi masalah kesehatan masyarakat secara global. Penyakit ini ditandai dengan penurunan fungsi ginjal yang progresif dan irreversibel, sehingga pasien memerlukan perawatan jangka panjang seperti hemodialisis, dialisis peritoneal, atau terapi konservatif. Kondisi tersebut berdampak tidak hanya pada aspek fisik pasien, tetapi juga memengaruhi kondisi psikologis, sosial, dan ekonomi, baik bagi pasien maupun keluarga. Literature review ini bertujuan untuk menganalisis dan mensintesis hasil-hasil penelitian terkait pengaruh edukasi keluarga terhadap tingkat pengetahuan dan kesiapan keluarga dalam merawat pasien gagal ginjal kronik, sehingga dapat menjadi dasar pengembangan intervensi keperawatan berbasis keluarga serta meningkatkan kualitas pelayanan keperawatan. Literatur review ini bertujuan untuk mengkaji bukti ilmiah terkait pengaruh mobilisasi dini pasca operasi terhadap pemulihan pasien. Penelitian ini menggunakan desain literature review untuk mengkaji pengaruh edukasi keluarga terhadap tingkat pengetahuan dan kesiapan merawat pasien gagal ginjal kronik. Pencarian artikel dilakukan melalui beberapa basis data ilmiah, yaitu Google Scholar, PubMed, dan ScienceDirect. Kata kunci yang digunakan dalam pencarian artikel meliputi edukasi keluarga, pengetahuan keluarga, kesiapan merawat, gagal ginjal kronik, serta padanan kata dalam bahasa Inggris seperti family education, knowledge, caregiver readiness, dan chronic kidney disease. Kriteria inklusi dalam literature review ini meliputi artikel penelitian yang membahas edukasi keluarga pada pasien gagal ginjal kronik, menggunakan desain penelitian kuantitatif atau kualitatif, tersedia dalam teks lengkap (full text), serta dipublikasikan dalam kurun waktu sepuluh tahun terakhir. Artikel yang tidak relevan dengan topik, tidak tersedia dalam teks lengkap, atau berupa opini dan laporan kasus dikeluarkan dari kajian. Proses seleksi artikel dilakukan melalui beberapa tahap, yaitu identifikasi artikel berdasarkan judul dan abstrak, penilaian kesesuaian isi artikel dengan tujuan penelitian, serta telaah teks lengkap. Artikel yang memenuhi kriteria inklusi kemudian dianalisis secara naratif. Data yang diekstraksi meliputi penulis dan tahun publikasi, desain penelitian, jumlah sampel, bentuk intervensi edukasi keluarga, serta hasil penelitian terkait tingkat pengetahuan dan kesiapan merawat pasien gagal ginjal kronik. Analisis data dilakukan dengan cara membandingkan dan mensintesis hasil-hasil penelitian yang terpilih untuk memperoleh gambaran menyeluruh mengenai pengaruh edukasi keluarga terhadap tingkat pengetahuan dan kesiapan merawat pasien gagal ginjal kronik. Hasil literature review juga menunjukkan adanya variasi efektivitas edukasi yang dipengaruhi oleh metode penyampaian, durasi edukasi, dan karakteristik keluarga. Edukasi yang dilakukan secara berkelanjutan dan menggunakan kombinasi metode cenderung memberikan hasil yang lebih optimal dibandingkan edukasi satu kali atau tanpa media pendukung. Berdasarkan hasil literature review dapat disimpulkan bahwa edukasi keluarga berpengaruh positif terhadap peningkatan tingkat pengetahuan dan kesiapan keluarga dalam merawat pasien gagal ginjal kronik. Edukasi keluarga yang diberikan secara terstruktur dan berkesinambungan mampu meningkatkan pemahaman keluarga mengenai penyakit dan perawatan, serta meningkatkan kesiapan keluarga dalam menjalankan peran sebagai caregiver. Kata Kunci: Penyakit Ginjal Kronis, Pendidikan Pengasuh, Kesiapan Merawat, Media.